KOL Credibility Influence on Generation Z TikTok Skincare Purchase Decision-Making Process: Mediated by Brand Image and Digital Consumer Behavior - Mochammad Revo Izqulby; Syti Sarah Maesaroh; Asep Nuryadin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aimed to analyze the influence of Key Opinion Leader (KOL) Credibility on TikTok on the Purchase Decisions-Making Process of skincare products among Indonesian Generation Z, examining the mediating roles of Brand Image and Digital Consumer Behavior. Employing a quantitative, causal-correlational survey design, data were collected from 265 Indonesian Generation Z respondents (ages 15-25, 79.2% female, 90.2% daily TikTok users) interested in skincare, with KOL Credibility measured by expertise, trustworthiness, and attractiveness; Brand Image by brand associations; Digital Consumer Behavior by information search, engagement, and purchase intention; and Purchase Decision-Making Process by frequency and probability of purchase, analyzed using SPSS and PROCESS Macro Hayes. Results indicated that KOL Credibility significantly influenced Purchase Decision Making-Process directly (Direct Effect = .116, p=.005), and also significantly impacted Brand Image (.625) and Digital Consumer Behavior (.460), both of which positively and significantly influenced Purchase Decision- Making Process (.231 and .620 respectively). Bootstrapping confirmed the mediating roles of Brand Image (.144, CI: .064-.214) and Digital Consumer Behavior (.285, CI: .190-.374), with Digital Consumer Behavior showing a significantly larger mediating contribution. Implications suggest that skincare brands should focus on credible KOLs and content strategies that foster active digital engagement, contributing to digital marketing theory by highlighting the dominance of the Digital Consumer Behavior mediation pathway among young audiences